Efek Pupuk Bokashi Terhadap Pertumbuhan Dan Hasil Tanaman Terung Lokal (Solanum melongena L) - Josina Irene Brigetha Hutubessy; Kristono Yohanes Fowo; Murdaningsih Murdaningsih (Agriculture Faculty of Flores University, 2023)
Efforts to increase the growth and production of local eggplant (Solanum melongena L) through chicken manure bokashi fertilizer. Local eggplant or kiku/index eggplant is a type of vegetable plant that can be eaten raw as fresh vegetables and processed with various foods with high nutritional value. The purpose of this study was to study the response of the local eggplant (index finger eggplant) to the different doses and to obtain the optimum dose of chicken manure bokashi fertilizer on the growth and yield of the index finger eggplant. In the study, a randomized block design (RBD) was used with a single factor pattern consisting of 6 treatments of Bokashi Chicken Manure, namely: BA0 = 0 tons/ha, BA1 = 10 tons/ha or 8.4 kg/plot, BA2 = 20 tons/ha ha or 16.8 kg/plot, BA3 = 30 tons/ha or 25.2 kg/plot, BA4 = 40 tones/ha or 33.6 kg/plot, BA5= 50 tons/ha or 42 kg/plot and BA6 = 60 tons/ha or 50.4 kg/plot. Observed variables; plant height (cm), number of leaves leaf area (cm2), fruit diameter (cm), fruit weight per plant (g), and fruit weight per hectare (tons). Dosage of chicken manure bokashi fertilizer 60 tons/ha or 50, 4 kg/plot produced an average plant height of 18.61 cm; the number of leaves 11.09 leaves; leaf area of 791.78 cm²; fruit Diameter of 2.52 cm; The weight of the fruit planted is 0.27 g and the fruit per hectare is 6.48 tons. Applying chicken manure bokashi fertilizer can increase local eggplant growth and yield with an average increase, in plant height by 0.32%, number of leaves by 0.45%, leaf area by 0.11%, fruit diameter by 0.024%, fruit weight per hectare by 0.21 %.